Physical fitness and performances of an amputee cycling world champion: a case study - Menaspà, P.; Rampinini, E.; Tonetti, L.; Bosio, L. (International Journal of Sports Physiology and Performance, 2012)
Purpose: To describe the physical fitness of a top-level lower limb amputee (LLA) cyclist and paracycling time-trial (TT) race demands. Methods: The 40-y-old male unilateral transfemoral amputee TT World Champion was tested in a laboratory for peak oxygen uptake (VO2peak), ventilatory threshold (VT2), power output (PO), and hemoglobin mass (Hb-mass). Moreover, several measures (eg, PO, heart rate [HR], cadence) were collected during 4 international TT competitions in the same season. The races` intensity was evaluated as time spent below, at, or above VT2. Results: The cyclist (1.73 m, 55.0 kg) had a VO2peak of 3.372 L/min (61.3 mL/ kg.min). The laboratory peak PO was 315 W (5.7 W/kg). The maximal HR was 208 beats/min, and his Hb-mass was 744 g (13.5 g/kg). The TTs were meanly 18 ± 4.5 km in length, and the mean PO was 248 ± 8 W with a cadence of 92 ± 1 rpm. During the TTs, the cyclist spent 23% ± 9% of total time at VT2, 59% ± 10% below, and 18% ± 5% above this intensity. Conclusions: The subject`s relative VO2peak is higher than previously published data on LLA, and surprisingly it is even higher than "good" ACSM normative data for nondisabled people. The intensity of the races was found to be similar to cycling TTs of the same duration in elite female cyclists. These results might be useful to develop specific training schedules and enhance performance of LLA cyclists.